2014
DOI: 10.1161/atvbaha.114.303240
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Initial Functional Characterization of a Human Vascular Cell–Enriched Long Noncoding RNA

Abstract: Objective Long non-coding RNAs (lncRNAs) represent a rapidly growing class of RNA genes with functions related primarily to transcriptional and post-transcriptional control of gene expression. There is a paucity of information about lncRNA expression and function in human vascular cells. Thus, we set out to identify novel lncRNA genes in human vascular smooth muscle cells and to gain insight into their role in the control of smooth muscle cell phenotypes. Approach and Results RNA-sequencing of human coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
232
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(239 citation statements)
references
References 74 publications
5
232
1
1
Order By: Relevance
“…Using of RNA-sequencing studies, Bell et al 65) revealed 31 unannotated lncRNAs from human coronary artery smooth muscle cells and investigated a lncRNA SENCR (smooth muscle and endothelial cell enriched migration/differentiation-associated lncRNA). SENCR knockdown decreased myocardin al 72) identified a dendritic cell-specific lncRNA termed lnc-DC playing a critical role in the differentiation of dendritic cells from human monocytes and mouse bone marrow, a cell type playing important roles in atherosclerosis 73) .…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 99%
“…Using of RNA-sequencing studies, Bell et al 65) revealed 31 unannotated lncRNAs from human coronary artery smooth muscle cells and investigated a lncRNA SENCR (smooth muscle and endothelial cell enriched migration/differentiation-associated lncRNA). SENCR knockdown decreased myocardin al 72) identified a dendritic cell-specific lncRNA termed lnc-DC playing a critical role in the differentiation of dendritic cells from human monocytes and mouse bone marrow, a cell type playing important roles in atherosclerosis 73) .…”
Section: Long Noncoding Rnas In Smcsmentioning
confidence: 99%
“…5 lncRNAs display high organ and cell specificity and are involved in maintaining cell integrity. Previous analyses of cardiovascular lncRNAs were performed in cultured cells, [6][7][8] animal models, 9,10 and human heart biopsies. 10,11 Circulating lncRNAs have been suggested as potential biomarkers for cancer, but few studies have explored lncRNAs as biomarkers in the context of cardiovascular disease.…”
Section: Article See P 668mentioning
confidence: 99%
“…[6][7][8]12,15 With the exception of MIAT, all analyzed lncRNAs were differentially expressed in patients with MI: antisense hypoxia inducible factor 1α, KCNQ1OT and MALAT1 were upregulated, whereas ANRIL was downregulated. MALAT1 and antisense hypoxia inducible factor 1α are known to be induced under hypoxia.…”
Section: Circulation Research September 12 2014mentioning
confidence: 99%
“…72 Contrarily, the finding that their promoters are often highly conserved 73 and their expression is AAV9 indicates adeno-associated viruses; AngII, angiotensin II; CTGF, connective tissue growth factor; Fbln2, fibullin-2; FoxO3, forkheadbox O3; MeCP2, methyl-CpG-binding protein 2; MHC, myosin heavy chain; MI, myocardial infarction; PTEN, phosphatase and tensin homolog; RasGAP, Ras-GTPase activating protein; SPRY, Sprouty homologue 1; TAC, transverse aortic constriction; and TGFβ, transforming growth factor-β. by guest on May 10, 2018 http://circres.ahajournals.org/ Downloaded from generally more tissue-specific than protein-coding genes does suggest a functional relevance for at least some of them. 74 In fact, functional studies have revealed that lncRNAs participate in a variety of biological processes, including transcriptional regulation by recruiting chromatin regulatory proteins to specific genomic locations, genomic imprinting, organization of protein complexes, and shaping distinct nuclear structures.…”
Section: Lncrnas As New Players In Cardiac Biologymentioning
confidence: 98%
“…83 In endothelial cells and smooth muscle cells, several lncRNAs (ie, MALAT1 and SENCR) have been shown to control migration and differentiation. 84,85 In fibroblasts, TERRA lncRNAs (eg, telomeric repeat-containing RNA) are implicated in modulating the structure and processing of deprotected telomeres. 86,87 Deprotected telomeres elicit a DNA damage response leading to chromosome instability, which is in turn associated with cellular senescence.…”
Section: Lncrnas As New Players In Cardiac Biologymentioning
confidence: 99%